If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 + -2x + 1 = 0 Reorder the terms: 0 + 1 + -2x = 0 Combine like terms: 0 + 1 = 1 1 + -2x = 0 Solving 1 + -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 0 + -1 -2x = 0 + -1 Combine like terms: 0 + -1 = -1 -2x = -1 Divide each side by '-2'. x = 0.5 Simplifying x = 0.5
| 2w-6=126 | | z-4z=9z-6-z | | (-7+8x)-(x-1)=3x+6 | | 6x-1=2x-21 | | 25.94=5g+3.69 | | z+6=-17 | | 2(3x)+2(x)=320 | | 175-75+48750=50750-150 | | 3x(9-8)+7-11= | | 12z-4z+8=-16 | | 7z-z=-1+3z-1-1 | | 4x+3=6+2x+25 | | 4x^2+4x-5=2x(x+3)-1 | | 1.52g-11=0.40 | | -2-2x=6x-50 | | 0.24p+1.17=1.8 | | 45+90x=585 | | 9x+8y=13.83 | | -5r-5r=4-8r-4r | | 48750-75+175=50750-150 | | 0.24p+1.17=1.29 | | -2x-6=2(2x-3) | | x=6.9375+-0.4375y | | -9=3(-c+2) | | 1X+4X=58 | | -20(y+2)+6(4y-4)=3(y-6)+12 | | -0.24p+1.602=1.8 | | 12x-3=4x | | 3(x-2)-4=4x-2 | | 9y=2y+35 | | v^2-2=65 | | 2y+1=23 |